Risiko likuiditas di perbankan syariah: Pendekatan inovatif dalam mengukur, mengelola, dan meminimalkan dampaknya - Ramadhani, Sri Wahyu (Maliki Interdisciplinary Journal, 2024)
Islamic banks, as financial institutions engaged in gathering and distributing funds, are invariably accompanied by risks that may have both positive and negative impacts on the bank, one of which is liquidity risk. The purpose of this study is to understand liquidity risk and liquidity risk management in Islamic banks. The research approach used is literature review. The results of this study reveal that liquidity risk, which threatens banks when they are unable to meet their maturing obligations, is triggered by environmental factors and policies. To mitigate this risk, Islamic banking institutions need to understand and control their liquidity through active supervision and the implementation of effective risk management policies and systems.